Society of Behavioral Medicine (SBM) position statement: End the fatal paradox: change the names of our Federal Institutes on Addiction. Issue 5 (1st December 2020) - Kelly, John F; Earnshaw, Valerie
Abstract: Evidence demonstrates that exposure to the terms "abuse" and "substance abuser" increases stigmatizing and discriminatory attitudes toward individuals suffering from drug and alcohol problems, ultimately leading to suboptimal clinical care delivery and poorer treatment outcomes. The American Psychiatric Association has dropped the term "abuse" from its diagnostic terminology; therefore, the term provides no advantage in terms of clinical precision or public health communication. Although numerous medical and public health associations have advocated against the term "abuse, " it remains embedded in the very titles of our major federal institutions and administrations whose explicit mission is to alleviate these endemic problems. Congress must act to change the names of the National Institutes of Health on addiction (i.e., NIAAA, NIDA) and related federal institutions (SAMHSA, CSAT). The Society of Behavioral Medicine supports the removal of the term "abuse" from the National Institutes of Health and related federal administrations pertaining to addiction and replacement with more neutral and nonstigmatizing terminology (e.g., disorder). Alternative names for the federal organizations that SBM supports are the "National Institute on Alcohol Use Disorder, " the "National Institute on Drug Use Disorders, " the "Substance Use Disorder and Mental Health Services Administration, " and the "Center for Substance Use Disorder Treatment." Abstract : Research demonstrates that the term "abuse", embedded in the names of our national institutes on addiction, induces stigma. It is time to change their names.